Problems and Prospects of Regulation of Water Resources of the Aral Sea Basin - MUSABEKOV, Kambar; NURASHEVA, Kulyanda; MERGENBAYEVA, Aziza (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018DO - 10.14505//jarle.v9.1(31).22, 2018)
The purpose of the study is to analyze the causes of economic, social and environmental tensions in the development of the Central Asian countries of the Aral Sea basin. Using the method of economic and geographical research allowed identifying the problems of the region, the causes of depletion of water resources. Although the water-energy and resource potential is sufficient, there is a water deficit due to the irrational use of trans boundary rivers. As a result of the analysis of global competitiveness and innovation of economies, these countries are classified as the poorest. Measures are proposed for environmental sustainability and biological productivity of the Aral Sea ecosystem. It is recommended to conduct a full analysis of the legal framework on the Aral Sea basin, inventory of existing legal instruments with a view to eliminating contradictions and discrepancies in the implementation of development programs for the Central Asian region.